Association between youth homicides and state spending: a Chicago cross-sectional case study. Issue 1 (24th January 2022) - Mason, Maryann; McLone, Suzanne; Monuteaux, Michael C; Sheehan, Karen; Lee, Lois K; Fleegler, Eric W
Abstract : Objective: To identify contributing factors associated with rapid spikes and declines in Chicago youth homicide from 2009 to 2018. Setting: City of Chicago, Illinois, US 2009–2018. Participants: Homicide count data come from the National Violent Death Reporting System. The study included information on 2271 homicide decedents between the ages of 15 and 24 who died between 1 January 2009 and 31 December 2018. Of these decedents, 92.9% were male; 79.1% were non-Hispanic black; and 94.9% died from a firearm injury. Primary and secondary outcome measures: (A) Temporal shifts in monthly homicide rates and (B) temporal associations between social, environmental and economic conditions/events and fluctuations in homicides. Results: We found statistically significant shifts in homicide rates over time: a 77% rise in monthly youth homicide rates per 100 000 persons from 2015 to 2016 (4.3 vs 7.5); dropping back to pre-2015 rates (4.3) by mid-2017. There was a temporal co-occurrence between the rapid rise in youth homicides and absence of a state budget. Conversely, we found a temporal co-occurrence of the sharp decline in homicides with the reinstatement of a state budget. Adjusting for seasonality, we found death rates were greater in the months without a budget compared with months with a budget (1.48, 95% CI 1.29 to 1.70). Conclusions: Our findings suggest that state funding may be a potential protective factor against youth homicide.